Della Rati Saputri Tinjauan Lama Waktu Ketersediaan Rekam Medis Rawat Jalan Di RSUD Kota Depok - Della Rati Saputri della; Lily Widjaja lily; Laela Indawati laela; Nanda Aula Rumana nanda (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Medical records are files in which there are documents about the patient's identity and records of the results of examinations, actions, treatment, and other services that have been provided to patients. Medical records are very useful in providing services to patients because they contain written evidence in paper form for the services provided by doctors and other health workers. Therefore, medical records must be stored in appropriate storage places so that they can be obtained and made available quickly when needed again. Minimum Service Standards are the quality of basic services used in providing medical records with a minimum service standard time of providing outpatient medical records, which is ?10 minutes. This research was conducted at the Depok City Hospital, West Java. This study aims to determine the length of time the availability of outpatient medical records at the Depok City Hospital. This study uses a descriptive method with a quantitative approach by conducting interviews and observations. The population in this study was outpatient visits for 1 month in March 2022. The sample in this study was 106 requests for outpatient medical records using incidental sampling technique. The results of the study showed that ?10 minutes was 51 (48%), and the retrieval time of medical records >10 minutes was 55 (52%) divided into categories for retrieval time of 11 - 20 minutes by 25 (23,6%), 21 - 30 minutes by 8 (7,6%), and > 30 minutes by 22 (20,8%). With an average availability time of 17,42 minutes.